#TITLE_ALTERNATIVE# - BURHAN (NIM 12304019); Pembimbing : Dr. Eng. T. A. Sanny dan Dr. rer. nat. R. M. Rahmat Sule, NURUL
The quality of zero offset stack profile has a very significant role because that is the first profile that can be interpreted before migration process. One of the stack methods that can give a better result is Common Reflection Surface (CRS) stack. This method uses some ideas and principals from convensional CMP stacking. The difference is the CRS stack method using more number of trace than CMP stack method. In order to show that CRS method is better than conventional stacking, a comparation between result from CRS and conventional stacking was done in synthetic data. Synthetic data wes derived from the ray tracing seismic modelling. Then it processed by conventional and CRS stack method. The result from those processing are compared each other. This work demonstrate that in qualitative way, CRS method could give better subsurface imaging in than the conventional one. These seismic sections was migrated in the depth domain using Kirchhoff migration. The velocity model itself was built using CRS stack attributes. Efficiency as well as image quality of this process strongly depend on the selection of the migration aperture. The optimum migration aperture was known from stationery point and the aperture width around stationary, were defined from these attributes. So the effect beyond these aperture that contribute only noise to the migrated image was unused. Processing data using minimum-aperture Kirchhoff migration was applied to conventional and CRS stack sections. The result of the poststack migration show that it was influenced by the stacking section data, so poststack migrasion using CRS stack data are better than conventional one. If we want more detail in the structur image then we need to perform prestack migration. This migration was using multicoverage data and velocity model that was created before. These prestack data has more detail structure, but there are some noise effect in the migrated section.